2017
DOI: 10.1017/jog.2017.41
|View full text |Cite
|
Sign up to set email alerts
|

Melt-under-cutting and buoyancy-driven calving from tidewater glaciers: new insights from discrete element and continuum model simulations

Abstract: ABSTRACT. The simple calving laws currently used in ice-sheet models do not adequately reflect the complexity and diversity of calving processes. To be effective, calving laws must be grounded in a sound understanding of how calving actually works. Here, we develop a new strategy for formulating calving laws, using (a) the Helsinki Discrete Element Model (HiDEM) to explicitly model fracture and calving processes, and (b) the continuum model Elmer/Ice to identify critical stress states associated with HiDEM cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
158
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(174 citation statements)
references
References 50 publications
9
158
2
Order By: Relevance
“…Benn et al (2017) compared HiDEM calving for specified undercuttings of different sizes and showed that calving magnitude increases with undercutting size. For small undercuttings, calving simply removes part of the overhang, but for large undercuttings calving removes all of the overhang plus additional ice.…”
Section: Calving Modelmentioning
confidence: 99%
“…Benn et al (2017) compared HiDEM calving for specified undercuttings of different sizes and showed that calving magnitude increases with undercutting size. For small undercuttings, calving simply removes part of the overhang, but for large undercuttings calving removes all of the overhang plus additional ice.…”
Section: Calving Modelmentioning
confidence: 99%
“…If calving events are consistently smaller than the cavity, long-term frontal ablation rates will simply be determined by the submarine melt rate. On the other hand, stress migration effects may trigger calving events larger than the submarine cavity, in which case longterm frontal ablation rates will be greater than the submarine melt rate [5,6]. In addition, localized melt-undercutting may encourage calving of other parts of the glacier front.…”
Section: Processes Of Frontal Ablationmentioning
confidence: 99%
“…This snapshot shows the propagation of narrow fractures upward from the centres of the concentration in tensile stress at the base. Modified from Benn et al [5] plumes and the effects of ice mélange. When applied to Store Glacier, the model impressively replicates seasonal fluctuations of the glacier front without the need for model tuning [30].…”
Section: Modellingmentioning
confidence: 99%
See 2 more Smart Citations